Answer:
Not equal so b
Step-by-step explanation:
3(3+4)=21 3³=27
Answer:
B
Step-by-step explanation:
The formula for finding the relationship between a secant and a tangent is
tangent length ^2 = external segment secant/full length of secant
In this case
60^2 = 48*(x + 48) Expand
3600 = 48*(x + 48) Remove the brackets/
3600 = 48x + 48^2 Expand
3600 = 48x + 2304 Subtract 2304 from both sides
3600 - 2304 = 48x
1296 = 48x Divide both sides by 48
1296 / 48 = x
x = 27
(32•7a3b2)
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "^-4" was replaced by "^(-4)".
Step by step solution :
Step 1 :
Equation at the end of step 1 :
0-(((9•(a2))•(b6))•(0-7ab(-4)))
Step 2 :
Equation at the end of step 2 :
0 - ((32a2 • b6) • -7ab(-4))
Step 3 :
Final result :
(32•7a3b2)
I think its like this ,Tho hope it helped
4x5-2x3-3x2-7 descending means basically the same thing as greatest to least